Relationship of Family Support and Communication to Elderly Participation in the Work Area of the Sempaja Health Center, Samarinda City - Ariani, Wenty Ika; Noorbaya, Siti; Mayangsari, Rr. Nindya (Jurnal Sains dan Teknologi, 2023)
An increase in the number of elderly occurs in almost every country, both developing and developed countries. Along with increasing life expectancy, the number of elderly people in Indonesia tends to increase. To monitor the condition of the elderly both from their physical and mental health, they can be monitored by holding a special posyandu for the elderly. This research is to analyze the relationship between family support and communication on elderly participation in elderly posyandu in the Sempaja Community Health Center Working Area, Samarinda City. The research method used is an analytical survey with a cross-sectional design. Test the hypothesis using chi-square. The research results showed that 110 respondents (56.7%) did not support it, 84 respondents (43.3%) supported it. 111 respondents (57.2%) did not actively participate, 83 respondents (42.8%) actively participated. The results of the hypothesis test show that there is a relationship between family support and communication on elderly participation in the elderly posyandu in the Sempaja Community Health Center Working Area with a p-value = 0.000< (α=0.05) so that H0 is rejected and Ha is accepted, meaning that there is a significant relationship between support and Family communication regarding elderly participation in elderly posyandu. The conclusion is that the more the family supports and communicates well, the more actively the elderly will participate in the elderly posyandu and conversely, the more the family does not support and communicate, the less active the elderly will be in the elderly posyandu.